Optimistic Concurrency Control for multihop sensor networks - Soysal, O.; Aydin, B. I.; Demirbas, M. (2011 7th International Wireless Communications and Mobile Computing Conference, 2011)
In this study, we provide a lightweight singlehop primitive, Read-All-Write-Self (RAWS), that achieves optimistic concurrency control. RAWS guarantees serializability, which simplifies implementation and verification of distributed algorithms, compared to the low level message passing model. We also present a self-stabilizing multihop extension of RAWS, called Multihop Optimistic Concurrency Control Algorithm (MOCCA), to address the challenges of multihop networks. We implement RAWS on motes and investigate the effects of message loss over this novel primitive.